(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article traces the history of choral troparion operation since the origin until todaу. Served the classification troparions. The research was conducted based on lexographical souces, covering XI–XXI centuries, and written records of the church.